Detailed investigations into the Akabori–Momotani reaction for the synthesis of amphetamine type stimulants: Part 2. (June 2018) - Doughty, David; Kent, Emma; Painter, Ben; Pigou, Paul E.; Johnston, Martin R.
Highlights: Substituted benzaldehydes convert into pseudoephedrines. Electronic influence of the substituent on reaction outcomes was minor. Molecular modelling provides insight into substituents lack of influence. Sub-optimal reaction conditions with p -methoxy benzaldehyde produce new by-products. Stereochemical purity of products rationalised by molecular modelling. Abstract: The Akabori–Momotani reaction can be used to synthesise pseudoephedrine in 50% yield from N-methylalanine and benzaldehyde. This paper investigates electronic effects of substituted benzaldehydes on the reaction to synthesise amphetamine type stimulants and identifies several new Akabori–Momotani by-products, 1-[(4-methoxybenzyl)(methyl)amino]ethanol (11c), 2-(4-methoxyphenyl)-3, 4-dimethyl-1, 3-oxazolidine(12c), 1, 2, 3, 4-tetramethyl-5, 6-di-(4-methoxyphenyl)piperazine (13c ) and 1, 2, 4, 5-tetramethyl-3, 6-di-(4-methoxyphenyl)piperazine (14c ). This paper also investigates pseudoephedrine and methamphetamine isomeric distribution from the Akabori–Momotani reaction with the aid of molecular modelling to understand why more pseudoephedrine than ephedrine is produced.